Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Karyawan pada PT. Federal International Finance (FIF) Jakarta - Yuli Wahyudi (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study aims to determine the effect of training and work discipline on employee performance at PT. Federal International Finance (FIF) Jakarta. The method used is explanatory research with a sample of 82 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, training has a significant effect on employee performance by 35.1%, the hypothesis testing obtained a significance of 0.000 <0.05. Work discipline has a significant effect on employee performance by 42.5%, the hypothesis test obtained a significance of 0.000 <0.05. Training and work discipline simultaneously have a significant effect on employee performance by 51.4%, the hypothesis test obtained a significance of 0.000 <0.05.